Microstructural evolution, deformation modes, and failure mechanisms in laser powder bed fusion processed nickel-free and 316L stainless steels - Suman, Siddharth; Goel, Sneha; Rantala, Juhani; Nurmela, Asta; Anand, Abhinav; Ganvir, Ashish; Sui, Ran; Que, Zaiqing (Elsevier BV, 2026)
This study investigates the influence of microstructures on mechanical behavior and failure mechanisms of laser based powder bed fusion processed nickel-free and 316L stainless steels using small punch testing, nanoindentation, and miniaturized tensile testing. The as-printed 316L with a fully austenitic structure and high-density dislocation cells exhibited a nanohardness of 3.0 GPa, tensile strength of 600 MPa, and elongation close to 60 %, with failure occurring through ductile microvoid coalescence. In contrast, the as-printed nickel-free stainless steel with a fully ferritic matrix and random dislocation networks showed a high nanohardness of 4.94 GPa, but poor ductility of 2 % and transgranular cleavage fracture. Heat treatment at 950 °C for 30 min transformed the nickel-free steel into a duplex microstructure (56 % ferrite and 41 % austenite, with a minor 3 % Chi phase), reducing dislocation density and inducing stacking faults. This resulted in moderate improvement in tensile strength as well as ductility and a mixed fracture mode. Post-mortem analysis revealed that Chi phase assisted crack initiation and strain localization was observed near coarse grains. The evolution of low-angle to high-angle grain and twin boundaries promoted plastic deformation. These results highlight the importance of phase engineering and microstructural control in optimizing the ductility and toughness of nickel-free steels.